Effects of food supplementation on cognitive function, cerebral blood flow, and nutritional status in young children at risk of undernutrition: randomized controlled trial. (22nd July 2020) - Roberts, Susan B; Franceschini, Maria A; Silver, Rachel E; Taylor, Salima F; de Sa, Augusto Braima; Có, Raimundo; Sonco, Aliu; Krauss, Amy; Taetzsch, Amy; Webb, Patrick; Das, Sai Krupa; Chen, C-Y; et al.
Abstract: Objective: To assess the effects of food supplementation on improving working memory and additional measures including cerebral blood flow in children at risk of undernutrition. Design: Randomized controlled trial. Setting: 10 villages in Guinea-Bissau. Participants: 1059 children aged 15 months to 7 years; children younger than 4 were the primary population. Interventions: Supervised isocaloric servings (≈1300 kJ, five mornings each week, 23 weeks) of a new food supplement (NEWSUP, high in plant polyphenols and omega 3 fatty acids, within a wide variety and high fortification of micronutrients, and a high protein content), or a fortified blended food (FBF) used in nutrition programs, or a control meal (traditional rice breakfast). Main outcome measurements: The primary outcome was working memory, a core executive function predicting long term academic achievement. Additional outcomes were hemoglobin concentration, growth, body composition, and index of cerebral blood flow (CBFi ). In addition to an intention-to-treat analysis, a predefined per protocol analysis was conducted in children who consumed at least 75% of the supplement (820/925, 89%). The primary outcome was assessed by a multivariable Poisson model; other outcomes were assessed by multivariable linear mixed models. Results: Among children younger than 4, randomization to NEWSUP increased working memory compared with the control meal (rate ratio 1.20, 95% confidence interval 1.02 to 1.41, P=0.03), with a larger effect in the per protocol population (1.25, 1.06 to 1.47, P=0.009). NEWSUP also increased hemoglobin concentration among children with anemia (adjusted mean difference 0.65 g/dL, 95% confidence interval 0.23 to 1.07, P=0.003) compared with the control meal, decreased body mass index z score gain (−0.23, −0.43 to −0.02, P=0.03), and increased lean tissue accretion (2.98 cm 2, 0.04 to 5.92, P=0.046) with less fat (−5.82 cm 2, −11.28 to −0.36, P=0.04) compared with FBF. Additionally, NEWSUP increased CBFi compared with the control meal and FBF in both age groups combined (1.14 mm 2 /s×10 −8, 0.10 to 2.23, P=0.04 for both comparisons). Among children aged 4 and older, NEWSUP had no significant effect on working memory or anemia, but increased lean tissue compared with FBF (4.31 cm 2, 0.34 to 8.28, P=0.03). Conclusions: Childhood undernutrition is associated with long term impairment in cognition. Contrary to current understanding, supplementary feeding for 23 weeks could improve executive function, brain health, and nutritional status in vulnerable young children living in low income countries. Further research is needed to optimize nutritional prescriptions for regenerative improvements in cognitive function, and to test effectiveness in other vulnerable groups. Trial registration: ClinicalTrials.gov NCT03017209 .